REGIONAL BASED KKN MANAGEMENT: TOWARD FREEDOM OF LEARNING DURING THE COVID-19 PANDEMIC - Ainur Rifqi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This research aims to reveal the management of KKN conducted by the KKN Center of State University of Surabaya during the covid-19 pandemic. This research was conducted using qualitative approach with the type of research used is a case study. Data retrieval is conducted through interviews, observations, and document studies. This research shows that KKN activities conducted are regional-based KKN activities with 1) student kkn and DPL regional placement planning tailored to the student's residential area when KKN is conducted, as well as KKN activities directed to help the community in preventing the spread of Covid-19 and solving problems that occurred during the Covid-19 Pandemic; 2) KKN activities are carried out with attention to health protocols, by implementing 5 forms of programs; and 3) evaluation of KKN activities is conducted through monitoring and evaluation with kkn center to determine the follow-up of KKN in the future. The entire management process of regional-based KKN is carried out by implementing health protocols.